Fundamental performance bounds for multi-performance criteria in wireless ad hoc networks - Qi WANG; Jaffrès-Runser Katia; Yi SUN; Jun LI; Jun ZHANG; Bin DA; Zhong-cheng LI (Tongxin xuebao)
In wireless ad hoc networks,the fundamental performance bounds could provide insight to improve network routing or resource allocation protocol as well as an upper bound against which to compare the performance of existing protocols.This work addresses the problem of deriving fundamental performance bounds including Pareto optimal upper and lower bounds for wireless ad hoc networks when multiple criteria including throughput,delay and energy are of interest.It is based on a performance evaluation framework composed of a broadcast and interference-limited network model.Fundamental performance bounds derived for a 1-relay and a 2-relay with multi-flow topologies are assessed through simulations.The model is validated with highest RMSE lower than 10-3.